The Qur'an's Ideal Teacher Profile - Amirrudin MS (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2023)
The point of this investigate is to investigate the Qur'anic concept of an perfect instructor profile. The Qur'an, as God's wonderful word, is exceedingly critical when utilized as an perfect parameter and, clearly, as a ponder protest. This inquire about utilizes a comprehensive survey of the writing and a subject elucidation approach. The comes about show that the Qur'an's wording for instructors is particularly far reaching; the term "educator" does not allude to a individual who as it were conveys instruction, but or maybe alludes to the meaning of the Qur'an's words. Murabbi, mu'allim, mu'addib, mudarris, mursyid, muzakki, and mubasyira wa nazira are all terms within the Qur'an that can be classified as instructors.